Question
upstudy study bank question image url

There are 10 terms in an arithmetic sequence. The sum of the terms in the even positions \( \left(a_{2}, a_{4}\right. \), etc.) is 25 , while the sum of the terms in the odd positions ( \( a_{1}, a_{3} \), etc.) is 10 . Find the \( 7^{\text {th }} \) term of this arithmetic sequence.

Ask by Schwartz Carrillo. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The 7th term of the arithmetic sequence is 8.

Solution

Let's solve the problem step by step. **Given:** - An arithmetic sequence with 10 terms. - Sum of the terms in even positions (\(a_2, a_4, a_6, a_8, a_{10}\)) is 25. - Sum of the terms in odd positions (\(a_1, a_3, a_5, a_7, a_9\)) is 10. **Let:** - \(a\) be the first term of the sequence. - \(d\) be the common difference. **Sequence Terms:** \[ a_1 = a \\ a_2 = a + d \\ a_3 = a + 2d \\ a_4 = a + 3d \\ \vdots \\ a_{10} = a + 9d \] **Sum of Even Position Terms:** \[ a_2 + a_4 + a_6 + a_8 + a_{10} = (a + d) + (a + 3d) + (a + 5d) + (a + 7d) + (a + 9d) \] \[ = 5a + (1 + 3 + 5 + 7 + 9)d \\ = 5a + 25d = 25 \quad \text{(1)} \] **Sum of Odd Position Terms:** \[ a_1 + a_3 + a_5 + a_7 + a_9 = a + (a + 2d) + (a + 4d) + (a + 6d) + (a + 8d) \] \[ = 5a + (0 + 2 + 4 + 6 + 8)d \\ = 5a + 20d = 10 \quad \text{(2)} \] **Solving the System of Equations:** Subtract equation (2) from equation (1): \[ (5a + 25d) - (5a + 20d) = 25 - 10 \\ 5d = 15 \\ d = 3 \] Substitute \(d = 3\) into equation (2): \[ 5a + 20(3) = 10 \\ 5a + 60 = 10 \\ 5a = -50 \\ a = -10 \] **Finding the 7th Term:** \[ a_7 = a + 6d \\ = -10 + 6(3) \\ = -10 + 18 \\ = 8 \] **Answer:** 8

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

Let the first term of the arithmetic sequence be \( a \) and the common difference be \( d \). The terms in the sequence can be represented as: - \( a_1 = a \) - \( a_2 = a + d \) - \( a_3 = a + 2d \) - \( a_4 = a + 3d \) - \( a_5 = a + 4d \) - \( a_6 = a + 5d \) - \( a_7 = a + 6d \) - \( a_8 = a + 7d \) - \( a_9 = a + 8d \) - \( a_{10} = a + 9d \) The sum of the terms in even positions is: \[ a_2 + a_4 + a_6 + a_8 + a_{10} = (a + d) + (a + 3d) + (a + 5d) + (a + 7d) + (a + 9d) \] This simplifies to: \[ 5a + (1 + 3 + 5 + 7 + 9)d = 5a + 25d \] According to the problem, this sum is 25: \[ 5a + 25d = 25 \quad \text{(1)} \] The sum of the terms in odd positions is: \[ a_1 + a_3 + a_5 + a_7 + a_9 = a + (a + 2d) + (a + 4d) + (a + 6d) + (a + 8d) \] This simplifies to: \[ 5a + (0 + 2 + 4 + 6 + 8)d = 5a + 20d \] According to the problem, this sum is 10: \[ 5a + 20d = 10 \quad \text{(2)} \] Now we have a system of equations: 1) \( 5a + 25d = 25 \) 2) \( 5a + 20d = 10 \) We can subtract equation (2) from equation (1): \[ (5a + 25d) - (5a + 20d) = 25 - 10 \] This simplifies to: \[ 5d = 15 \] Thus, we get: \[ d = 3 \] Now substituting the value of \( d \) back into equation (2): \[ 5a + 20(3) = 10 \] That becomes: \[ 5a + 60 = 10 \] Solving for \( a \): \[ 5a = 10 - 60 \] \[ 5a = -50 \] \[ a = -10 \] Now we have \( a = -10 \) and \( d = 3 \). We can find the \( 7^{\text{th}} \) term \( a_7 \): \[ a_7 = a + 6d = -10 + 6(3) = -10 + 18 = 8 \] Thus, the \( 7^{\text{th}} \) term of the arithmetic sequence is \( \boxed{8} \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy